Microencapsulation and its Effects on Quality and Shelf Life of Prawn Larval Feed - Rema MK (Department of Processing Technology, College of Fisheries, 1998)
Three microencapsulated diets have been prepared using clam meal as the protein source and collagen and gelatin (extracted from fish skin waste) and commercially available egg albumin as the encapsulating material. Attempts were made to rear the larval prawn, M 'aorobrachium rosenbergii, with these diets and to study the effect of encapsulation on quality and shelf life of the encapsulated feeds. The results of the 15 days feeding trials showed that all the three encapsul- ated diets were acceptable to the larvae from V th stage onwards with survival rate ranging from 80-90 % which is comparable with that of live Artemia nauplii (90%) and the larvae also undergone moulting during the rearing period. The microbial analysis and the rancidity tests conducted to evaluate the shelf life of the feed showed that all the feeds remain in good condition after 45 days of storage except that the gelatin encapsulated diet showed a comparatively higher . number of microflora. However, the gelatin encapsulated diets showed permissible limit of rnicroflora after 15 days of storage. The peroxide and rnalonaldehyde content of the prepared diets were below the toxic level to affect the survival of the larvae, A definite tolerable level of rancidity in prawn feeds is not known. Hence, to find the lethal level of toxicity of oxidised feed further work has to be done in this field.